2003
DOI: 10.1091/mbc.e02-07-0411
|View full text |Cite
|
Sign up to set email alerts
|

Obscurin Is a Ligand for Small Ankyrin 1 in Skeletal Muscle

Abstract: The factors that organize the internal membranes of cells are still poorly understood. We have been addressing this question using striated muscle cells, which have regular arrays of membranes that associate with the contractile apparatus in stereotypic patterns. Here we examine links between contractile structures and the sarcoplasmic reticulum (SR) established by small ankyrin 1 (sAnk1), a approximately 17.5-kDa integral protein of network SR. We used yeast two-hybrid to identify obscurin, a giant Rho-GEF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
244
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(256 citation statements)
references
References 55 publications
11
244
1
Order By: Relevance
“…Of special interest is the fact that obscurin is present on the lateral surfaces of nascent myofibrils and between the forming narrow myofibril bundles. Yeast two-hybrid assay screening recently showed that obscurin interacts with small ankyrin 1, and immunolabeling revealed close localization of these two proteins in skeletal muscle fibers (Bagnato et al 2003;Kontrogianni-Konstantopoulos et al 2003;Armani et al 2006). Small ankyrin 1 is a ligand protein structurally associated with the sarcoplasmic reticulum (Porter et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of special interest is the fact that obscurin is present on the lateral surfaces of nascent myofibrils and between the forming narrow myofibril bundles. Yeast two-hybrid assay screening recently showed that obscurin interacts with small ankyrin 1, and immunolabeling revealed close localization of these two proteins in skeletal muscle fibers (Bagnato et al 2003;Kontrogianni-Konstantopoulos et al 2003;Armani et al 2006). Small ankyrin 1 is a ligand protein structurally associated with the sarcoplasmic reticulum (Porter et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this antibody was used in a large number of laboratories for detection of sarcomeric α-actinin in cardiac and skeletal muscle in vivo and in cell culture (e.g. Bagnato et al 2003;Sanger et al 2005;Musa et al 2006;Kontrogianni-Konstantopoulos et al 2003.…”
Section: Immunolabeling and Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The ␣-helix surface (residues 1773, 1777, 1780, 1784, and 1788) may also associate with signaling proteins such as GTPases or protein kinases, which may not be easily detected in conventional yeast two-hybrid assays (28,29). The giant Rho-guanine exchage factor obscurin has been reported to bind to a similar but not identical site in small ankyrin-1 (30,31). Therefore, the ankyrin-B amphipathic ␣-helix and surrounding residues may accommodate multiple protein interactions to regulate ankyrin-B function.…”
Section: Discussionmentioning
confidence: 99%
“…Obscurin is the third member of the family of sarcomeric giants, along with titin and nebulin, and contains Ig-Fn modules and multiple signaling domains [51,52]. While its localization in the sarcomere remains controversial [51], the interactions with titin [51], myosin [49] and ankyrin [53] suggest that, similar to its invertebrate ortholog Unc-89 [52], obscurin might provide an elastic connection between the M-band and the plasma membrane and/or between the M-bands of adjacent myofibrils.…”
Section: Extra-sarcomeric Stabilization Of the M-bandmentioning
confidence: 99%